Zero surface tension limit of the free-surface incompressible Euler equations with damping. (April 2018) - Lian, Jiali
Abstract: We consider the free boundary problem for a layer of an incompressible inviscid fluid in a uniform gravitational field, lying above a rigid bottom and below the atmosphere in a horizontally periodic setting. We establish the global-in-time zero surface tension limit of the problem with damping for the small initial data.